The SWOT Analysis-Based MSME Management Model - Fitriya, Sri; Emelinda, Emelinda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the foundation of the nation's economy, but their development has been less than promising due to poor management of their operations. Inadequate management results in the inability of MSMEs to grow and improve their standards, and they struggle to manage their businesses effectively and efficiently. The tendency for MSMEs to be family-run contributes to a lack of professionalism in their operations. The long-term objective of this research is to develop a management model that can be practically applied by MSMEs to support productivity and business development. In general, MSME business management (marketing, production, human resources, and finance) can be implemented by providing training to MSME actors. Over time, MSMEs need to be closely monitored to ensure proper management practices are followed. Based on the SWOT analysis conducted, strategies have been identified to provide training in all aspects of management, considering the lack of knowledge within MSMEs. Introducing information technology is also an approach to technology-based marketing.